2007
DOI: 10.1111/j.1360-0443.2007.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of treatment on 3 years' outcome for heroin dependence: findings from the Australian Treatment Outcome Study (ATOS)

Abstract: At 3 years, there were impressive reductions in drug use, criminality, psychopathology and injection-related health problems following treatment exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 29 publications
7
104
2
1
Order By: Relevance
“…Many studies were excluded due to their sampling criteria. For example, many papers from the Australian Treatment Outcome Study included individuals attending needle exchange services who were not treated for their opiate problem (Darke, 2011;Darke et al, 2011;Darke et al, 2009;Teesson et al, 2015;Teesson et al, 2007). There is substantial variation in what the term "older" or "ageing" encompasses and, therefore, the body of evidence for the target population is small, and the majority of studies do not give their reasoning for their choice of age cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were excluded due to their sampling criteria. For example, many papers from the Australian Treatment Outcome Study included individuals attending needle exchange services who were not treated for their opiate problem (Darke, 2011;Darke et al, 2011;Darke et al, 2009;Teesson et al, 2015;Teesson et al, 2007). There is substantial variation in what the term "older" or "ageing" encompasses and, therefore, the body of evidence for the target population is small, and the majority of studies do not give their reasoning for their choice of age cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…These include the Drug Abuse Reporting Programme (DARP), Treatment Outcomes Prospective Study (TOPS), and Drug Abuse Treatment Outcomes Studies (DATOS) in the United States, [4] the National Treatment Outcomes Research Study (NTORS) in the United Kingdom, [5] the Australian Treatment Outcome Study in Australia, [6] and the Amsterdam Cohort in the Netherlands. [7] These studies showed that length of treatment predicts outcome, with treatment periods of >3 months showing higher rates and longer periods of abstinence.…”
Section: Articlementioning
confidence: 99%
“…Substitution treatments, by reducing rates of heroin use and protecting against withdrawal, can enable PWID to be more selective about the circumstances in which they inject (Koester, Anderson, & Hoffer, 1999), and have been associated with a reduction in needle sharing incidents (Gossop, Marsden, Stewart, & Kidd, 2003). Other positive outcomes include heroin overdose and criminal activity decreases (Marsch, 1998;Teesson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%